Relationship Rules with Word Vocabulary Writing Skills for Students - Hendrisman Hendrisman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to describe the relationship between vocabulary mastery and short story writing skills of Class IX students of SMPN 1, Guguak District, Lima Puluh Kota. This type of quantitative research using the method of population correlation in this study is a class IX. The research sample was taken using a cluster random sampling technique of 22 people. With the results of the study showed that the vocabulary mastery of Grade IX students was in the category of good qualifications with an average value of 80.45 on a range of 86-95% on a scale of 10. Second, short story writing skills are in more than adequate qualifications with an average value of 73 on a range of 66-75% on a scale of 10. Third, there is a significant relationship between the two variables because t arithmetic is greater than t table 2.3091 greater than 2,086. From the results of these correlations it can be concluded that there is a significant relationship between vocabulary mastery of short story writing skills Keywords: mastery, vocabulary, writing skills, short stories